Sedimentary record of a fluctuating ice margin from the Pennsylvanian of western Gondwana: Parana Basin, southern Brazil - Vesely, Fernando F.; Trzaskos, Barbara; Kipper, Felipe; Assine, Mario Luis [UNESP]; Souza, Paulo A. (Elsevier B.V., 2015)
The Parana Basin is a key locality in the context of the Late Paleozoic Ice Age (LPIA) because of its location east of the Andean proto-margin of Gondwana and west of contiguous interior basins today found in western Africa. In this paper we document the sedimentary record associated with an ice margin that reached the eastern border of the Parana Basin during the Pennsylvanian, with the aim of interpreting the depositional environments and discussing paleogeographic implications. The examined stratigraphic succession is divided in four stacked fades associations that record an upward transition from subglacial to glaciomarine environments. Deposition took place during deglaciation but was punctuated by minor readvances of the ice margin that deformed the sediment pile. Tillites, well-preserved landforms of subglacial erosion and glaciotectonic deformational structures indicate that the ice flowed to the north and northwest and that the ice margin did not advance far throughout the basin during the glacial maximum. Consequently, time-equivalent glacial deposits that crop out in other localities of eastern Parana Basin are better explained by assuming multiple smaller ice lobes instead of one single large glacier. These ice lobes flowed from an ice cap covering uplifted lands now located in western Namibia, where glacial deposits are younger and occur confined within paleovalleys cut onto the Precambrian basement. This conclusion corroborates the idea of a topographically-controlled ice-spreading center in southwestern Africa and does not support the view of a large polar ice sheet controlling deposition in the Parana Basin during the LPIA. (C) 2015 Published by Elsevier B.V.
Keywords: Late Paleozoic Ice Age; Glacial record; Ice marginal; Deglaciation; Itarare Group